Clinical Manifestation Summary of Common Comorbidity Conditions Associated with ASD - Zheng, Yinan (International Journal of Public Health and Medical Research, 2026)
Autism spectrum disorder is a heterogeneous neurodevelopmental disorder with problems in social communication and restricted or repetitive behaviours. However, there are often many other types of psychiatric diseases, neurological disorders, gastrointestinal diseases and sleep disorders in people who need help. List the main clinical features of frequent co-occurring disorders in autism in this paper. Psychiatric comorbidities, such as attention deficit hyperactivity disorder and anxiety disorders, may present as emotional dysregulation, impulsivity, avoidance behaviours and self-harm. Neurological diseases that cause repetitive movement disorders should be excluded first. Gastrointestinal disorders can be expressed indirectly, such as irritability, anger and poor sleep in children who are unable to communicate verbally. Sleep disorders will result in various mental and behaviour problems. Based on the above, it can be seen that the doctor should not assume autism is the cause of other diseases and disorders, but must also cooperate with other departments to conduct coordinated diagnosis and treatment.